Aimee Semple McPherson : everybody's sister - Blumhofer, Edith Waldvogel (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 1993)
One of the most influential and dynamic evangelists of the twentieth century, Aimee Semple McPherson (1890-1944) was a complex, lively, and controversial figure with a flair for the dramatic. Against the backdrop of the Roaring Twenties, Sister Aimee, as she was widely known, cultivated her ministry, preaching the "old-fashioned gospel" and calling for a return to simple biblical Christianity.
A religious leader who strongly identified with ordinary folk, she attracted hundreds of thousands of loyal followers throughout the United States and Canada.
Edith L. Blumhofer's thorough biography is grounded in extensive research and academic scholarship, yet written for the general reader as much as the historian. Blumhofer offers unique insights into McPherson's Canadian and Salvation Army roots and her relationship with Pentecostalism and uses her experiences to test stereotypes about mainstream Protestantism and Pentecostalism.
Blumhofer has also had access to resources not available to previous biographers - selected minutes of The International Church of the Foursquare Gospel - and she had contact with both of McPherson's children, Roberta Semple Salter and Rolf McPherson. Dozens of photographs also help illustrate McPherson's multiple roles as missionary, radio broadcaster, editor, mother, wife, and - above all - dramatic and inspiring evangelist.
Beginnings -- The pivot -- Full time -- Itinerating -- The foursquare gospel -- Content -- Angelus temple -- Angry surges roll -- Regrouping -- Finishing the course -- Epilogue -- A note on the sources -- Appendix: -- Excerpts from 'the bridal call' -- 'Motion picture actor converted' -- 'Delivered from a living death.'
Includes bibliographical references (p. 394-405) and index.
Keywords: McPherson, Aimee Semple, -- 1890-1944.; International Church of the Foursquare Gospel -- Clergy -- Biography; Evangelists -- United States -- Biography; Pentecostal churches -- United States -- Clergy -- Biography